Full-field measurements with Digital Image Correlation for vibro-impact characterisation. (July 2021) - Chabrier, R.; Sadoulet-Reboul, E.; Chevallier, G.; Foltête, E.; Jeannin, T.
Highlights: An experimental set-up (a ball between two plates) was designed to study vibro-impact phenomenon. Motion reconstruction is performed using Digital Image Correlation Technique. Coefficients of Restitution and friction forces are identified reliably. Results are confronted to simulations using a Hertz-damped model or a Coefficient of Restitution. Abstract: Vibro-impact (VI) based control strategies exploit non-linear phenomena occurring during impacts between oscillating masses and vibrating structures to mitigate vibrations. They are known to be effective on a wide frequency range, in harsh environnement, and they are eco-friendly in comparison to some visco-elastic polymers used for the same application. Different assumptions emerge to explain energy dissipation such as material and contact effects, or dynamic energy transfers between the structure and the oscillating masses acting as non-linear absorbers. As classical vibratory measurement tools do not allow to accurately and easily measure what happens in the contact area and the motion of the absorber, it is difficult to validate and quantify the phenomenon. The purpose of the study is to take advantage of full field measurements of the vibro-impact phenomenon to characterise a vibro-impact absorber and to better understand the interactions occurring during impact. To reach this objective, a dedicated experimental set-up has been designed and a method involving Digital Image Correlation (DIC) and a high-speed camera is used to capture and reconstruct the motion of the oscillating mass. The characterisation allows to estimate the Coefficient Of Restitution (COR) and friction forces, and provides data that are used in two different contact modelling strategies based on the COR and on the Hertz contact theory. The quantities identified in this paper enable to better understand the physical phenomena at stakes in a VI absorber.